Research on the Pleating Technique by Using Cardboard Pleat and Kraft Paper - Nguyen, Thi Ha Nguyen; Nguyen, Thi Luyen; Nguyen, Minh Nguyet; Tran, Thi Truc Linh (Journal of Technical Education Science, 2022)
Currently, the pleating technique is favored by famous fashion houses in the world and Vietnam because of its beauty and sophistication. This study aims to study pleating techniques, testing papers, and several polyester fabrics to form pleats under paper mold pressing by the manual heat-pressing method with three types of heat-pressed equipment such as steam iron, oven, and homemade heated box. One of the experiment results is a parameter table of the ability of fabrics and paper to pleat under certain conditions of temperature and time. Besides, a set of paper molds, a set of pleated fabric samples, and the above data table are also reference sources for major students or those who are interested in research, a collection, or a fashion project involving pleating techniques. The study is not only to add knowledge about new processing methods to the content of the material handling subject, but also to increase the ability to self-study, improve the subjectivity dynamic, and shorten self-study time in the process of creating new fashion models based on existing factory conditions.